Pengaruh Self-Efficacy Terhadap Pemecahan Masalah Aljabar Siswa dalam Pembelajaran Deep Learning - Nurrohmah, Siti Ulfiatun; Nugroho, Purna Bayu (Universitas PGRI Semarang, 2026)
This research aims to analyze the influence of self-efficacy on the algebraic problem-solving abilities of 7th-grade students at MTs Muhammadiyah Ogan Lima during the 2025/2026 academic year, specifically regarding algebraic problem-solving through the implementation of a deep learning approach. The study employs a quantitative method with a correlational design. Using a saturated sampling technique, the entire population of 35 students was selected as the study's respondents. Data collection instruments consisted of a self-efficacy questionnaire and an algebraic problem-solving skills test. Simple linear regression was selected as the data analysis technique, following the fulfillment of all prerequisite assumptions regarding normality and linearity. The analysis results confirm a significant positive influence of self-efficacy on algebraic problem-solving ability. The regression equation obtained is Ŷ = -2,829 + 0,404X, while the significance test shows a calculated 2,791 which exceeds the critical 2,035 at a significance level of 0,05. The coefficient of determination 0,191 demonstrates that self-efficacy accounts for 19% of the influence on students' ability to solve algebraic problems, while 81% is attributed to external factors. Thus, high student self-efficacy is shown to correlate with a significant improvement in their algebraic problem-solving ability.